Budesonide/formoterol MDI with co-suspension delivery technology in COPD: the TELOS study. Issue 3 (16th September 2018) - Ferguson, Gary T.; Papi, Alberto; Anzueto, Antonio; Kerwin, Edward M.; Cappelletti, Christy; Duncan, Elizabeth A.; Nyberg, Jack; Dorinsky, Paul
TELOS compared budesonide (BD)/formoterol fumarate dihydrate (FF) metered dose inhaler (BFF MDI), formulated using innovative co-suspension delivery technology that enables consistent aerosol performance, with its monocomponents and budesonide/formoterol fumarate dihydrate dry powder inhaler (DPI) in patients with moderate to very severe chronic obstructive pulmonary disease (COPD), without a requirement for an exacerbation history. In this phase III, double-blind, parallel-group, 24-week study (NCT02766608), patients were randomised to BFF MDI 320/10 µg (n=664), BFF MDI 160/10 µg (n=649), FF MDI 10 µg (n=648), BD MDI 320 µg (n=209) or open-label budesonide/formoterol DPI 400/12 µg (n=219). Primary end-points were change from baseline in morning pre-dose trough forced expiratory volume in 1 s (FEV1 ) and FEV1 area under the curve from 0–4 h (AUC0–4 ). Time to first and rate of moderate/severe exacerbations were assessed. BFF MDI 320/10 µg improved pre-dose trough FEV1 versus FF MDI (least squares mean (LSM) 39 mL; p=0.0018), and BFF MDI 320/10 µg and 160/10 µg improved FEV1 AUC0–4 versus BD MDI (LSM 173 mL and 157 mL, respectively; both p<0.0001) at week 24. BFF MDI 320/10 µg and 160/10 µg improved time to first and rate of moderate/severe exacerbations versus FF MDI. Treatments were well tolerated, with pneumonia incidence ranging from 0.5–1.4%. BFF MDI improved lung function versus monocomponents and exacerbations versus FF MDI in patients with moderate to very severe COPD. TELOS: co-suspension delivery technology budesonide/formoterol fumarate dihydrate in a metered dose inhaler improved lung function and time to first and rate of exacerbations versus monocomponents in patients with moderate to very severe COPD http://ow.ly/ffWo30lrJL6